Muslim and Gay: Seeking identity coherence in New Zealand - Tuffin K; Hopner V; Kahu ER (Taylor & Francis (Routledge), 2016)
The process of accepting oneself as gay and of ‘coming out’ to family and friends is well documented. For Muslim men, this is complicated by the tension between their emerging sexual identity and their religious and cultural birth identity, which labels homosexuality as sinful. This paper explores this process in a sample of five gay Muslim men living in New Zealand, a liberal secular society where homosexuality is widely accepted and gay rights are endorsed in legislation. Identity Process Theory drives the analysis, which identifies five themes encapsulating the process of striving for psychological coherence: resistance, acceptance, tension, renegotiation and pretence. Initial phases of denial and anger at their emerging sexuality are strongly linked to the conflict with their religious identity. Later, acceptance of their sexuality as natural and even God-given protects them from blame for their ‘sins’. In contrast to earlier work in the UK, for most men, renegotiation of their Muslim identity is adopted as the key strategy for achieving intrapsychic coherence. However, at an interpersonal level, families remain a source of conflict, temporarily resolved through pretence. Renegotiating religious identity leaves men having to pretend not just to be straight, but also to be strongly religious.
This is an Accepted Manuscript of an article published by Taylor & Francis in Culture, Health & Sexuality on 2015, available online: https://www.tandfonline.com/doi/full/10.1080/13691058.2015.1079927
Keywords: 1117 Public Health and Health Services; 1608 Sociology; 2002 Cultural Studies